An Assessment of Vitreous Degeneration in Eyes with Vitreomacular Traction and Macular Holes. (4th January 2017) - Ghadiali, Quraish; Zahid, Sarwar; Dolz-Marco, Rosa; Tan, Anna; Engelbert, Michael
Abstract : Purpose . To compare the stages of vitreous degeneration in patients with vitreomacular traction (VMT) and macular holes (MH). Methods . A retrospective study was performed analyzing stages of vitreous degeneration of eyes with VMT or MH using swept-source optical coherence tomography (SS-OCT) and spectral-domain optical coherence tomography (SD-OCT). An analogous review was performed on a control group of eyes with contralateral posterior vitreous detachments. Thirty-four eyes with VMT/MH and 39 control eyes were reviewed. Results. Twenty-seven VMT/MH eyes and 31 control eyes were included. Eyes with VMT/MH demonstrated significantly earlier stages of vitreous degeneration when compared to the control group (p = 0.048 ) despite significantly greater age (p = 0.032 ). Conclusions . Vitreoretinal interface disease is more often associated with a formed vitreous and an intact premacular bursa. This is contrary to previous assumptions implicating degeneration of vitreous as a precipitating factor of interface disease when in conjunction with abnormal vitreomacular separation.